Principles of town water supply and sanitation (The World Bank, 2007)
This report is a first attempt to set out a strategy for town water supply and sanitation. The primary objective is to identify, and find solutions for, the neglected towns those that fall between rural and urban, the two relatively well established approaches to managing water supply and sanitation services. Towns in the 2,000-50,000 population range generally fall within this "management gap;" they are the prime focus of this report. These towns face special challenges in the provision of their water and sanitation services.